PHOTO THERMAL INDUCED EFFECTS ON TESTES AND PITUITARY GONADOTROPIC CELLS DURING RESTING PHASE OF REPRODUCTIVE CYCLE IN A MURREL, CHANNA PUNCTATUS (BLOCH). - Singh, Ram; Chaturvedi, S. K.; Srivastava, S. J. (Journal of Indian Fisheries Association, 2010)
Effects of various combinations of photoperiod and temperature (NL-NT, LD 15:9-28C, NL 28C and LD 15:9 NT) were studied on testicular activity and pituitary gonadotropic cells in Channa punctatus during resting phase of reproductive cycle. Long photoperiod (LD 15:9-28ºC) and warm temperature (NL-28ºC) regimes were found to be more effective for testicular maturation and secretory activity of gonadotropic cell suggesting testicular maturation via brain – pituitary – testicular axis. Key words: Photoperiod, Temperature, Testes, Gonadotropic cell, Resting phase, Channa punctatus.